The Stemness Gene Mex3A Is a Key Regulator of Neuroblast Proliferation During Neurogenesis - Naef, Valentina; De Sarlo, Miriam; Testa, Giovanna; Corsinovi, Debora; Azzarelli, Roberta; Borello, Ugo; Ori, Michela (Frontiers in Cell and Developmental Biology, 2020)
Mex3A is an RNA binding protein that can also act as an E3 ubiquitin ligase to control gene expression at the post-transcriptional level. In intestinal adult stem cells, MEX3A is required for cell self-renewal and when overexpressed, MEX3A can contribute to support the proliferation of different cancer cell types. In a completely different context, we found mex3A among the genes expressed in neurogenic niches of the embryonic and adult fish brain and, notably, its expression was downregulated during brain aging. The role of mex3A during embryonic and adult neurogenesis in tetrapods is still unknown. Here, we showed that mex3A is expressed in the proliferative region of the developing brain in both Xenopus and mouse embryos. Using gain and loss of gene function approaches, we showed that, in Xenopus embryos, mex3A is required for neuroblast proliferation and its depletion reduced the neuroblast pool, leading to microcephaly. The tissue-specific overexpression of mex3A in the developing neural plate enhanced the expression of sox2 and msi-1 keeping neuroblasts into a proliferative state. It is now clear that the stemness property of mex3A, already demonstrated in adult intestinal stem cells and cancer cells, is a key feature of mex3a also in developing brain, opening new lines of investigation to better understand its role during brain aging and brain cancer development.